Language assessment literacy as self-awareness: Understanding the role of interpretation in assessment and in teacher learning. (July 2013) - Scarino, Angela
The increasing influence of sociocultural theories of learning on assessment practices in second language education necessitates an expansion of the knowledge base that teacher-assessors need to develop (what teachers need to know) and related changes in the processes of language teacher education (how they learn and develop it). Teacher assessors need to acquire concepts from diverse assessment paradigms; they need to learn to use these concepts in developing, using and analysing assessment procedures and results; they need to exercise critical perspectives on their own assessment practices for particular purposes in diverse contexts, especially in seeking to do justice to all in education. In this paper I argue that, to develop language assessment literacy with the dual goals of transforming teacher assessment practices and developing teacher understanding of the phenomenon of assessment itself and themselves as assessors, it is necessary to reconsider both the knowledge base and the complex processes of language teacher education. I draw on projects I have conducted on developing and investigating teacher understanding and practices in second language assessment, to discuss the need to work with the often tacit preconceptions, beliefs, understandings and world-views about assessment that teacher-assessors bring to teacher professional learning programs and that inform their conceptualizations, interpretations, judgments and decisions in assessment. I discuss the need in developing language assessment literacy for processes that develop teacher-assessors' capability to explore and evaluate their own preconceptions so as to become aware of how they interpret their own assessment practices and their students' second language learning. Through these processes they develop a deeper understanding of the interpretive nature of assessment and their own self-awareness as assessors.